Effects of an intradialytic resistance training programme on physical function: a prospective stepped-wedge randomized controlled trial. Issue 8 (28th December 2015) - Bennett, Paul Norman; Fraser, Steve; Barnard, Robert; Haines, Terry; Ockerby, Cherene; Street, Maryann; Wang, Wei Chun; Daly, Robin
Abstract: Background: Intradialytic exercise programmes are important because of the deterioration in physical function that occurs in people receiving haemodialysis. Unfortunately, exercise programmes are rarely sustained in haemodialysis clinics. The aim of this study was to determine the efficacy of a sustainable resistance exercise programme on the physical function of people receiving haemodialysis. Methods: A total of 171 participants from 15 community satellite haemodialysis clinics performed progressive resistance training using resistance elastic bands in a seated position during the first hour of haemodialysis treatment. We used a stepped-wedge design of three groups, each containing five randomly allocated cluster units allocated to an intervention of 12, 24 or 36 weeks. The primary outcome measure was objective physical function measured by the 30-s sit-to-stand (STS) test, the 8-foot timed up and go (TUG) test and the four-square step test. Secondary outcome measures included quality of life, involvement in community activity, blood pressure and self-reported falls. Results: Exercise training led to significant improvements in physical function as measured by STS and TUG. There was a significant average downward change ( β = −1.59, P < 0.01) before the intervention and a significant upward change after the intervention ( β = 0.38, P < 0.01) for the 30-s STS with a similar pattern noted for the TUG. Conclusion: Intradialytic resistance training can improve the physical function of people receiving dialysis.